ISTIHADHAH DAN PROBLEMATIKANYA DALAM KEHIDUPAN PRAKTIS MASYARAKAT - Ainun Barakah (CENDEKIA: Jurnal Studi Keislaman, 2015)
This research aims to determine kinds of istihadhah blood in islamic law and its implications in worship through studying on the literature of the classical books of fiqh Shafi'ites. The first step is to analyze the istihadhah problems experienced by some women, and then classified them in several cases so it can be distinguished among menstrual, childbed, and istihadhah blood, and ordinances of worship that be held in conditions of istihadhah, either prayer or fasting. This research use two approaches of introduction, first, the introduction of blood color and secondly, the introduction of menstrual cycle as well as a method to count, so based on the blood color and its cycle, it can be known about each woman’s classification of istihadhah blood case and its legal solution.